Treatment of olecranon fractures in childhood: A systematic review - De Maio, Fernando; Gorgolini, Giulio; Caterini, Alessandro; Luciano, Claudia; Covino, Dario; Farsetti, Pasquale (Frontiers in Pediatrics, 2022)
BACKGROUND Literature over the last 20 years provides evidence for a surgical treatment of displaced olecranon fractures in children, this is usually obtained with commonly proposed methods, although there is no general agreement about the best recommended technique. AIM Identifying the best surgical technique in displaced olecranon fractures in children and the role of associated fractures in the prognosis of these lesions, by analyzing the most relevant studies on this topic. METHODS A literature search was performed in MEDLINE database and Scopus database. Articles reporting clinical outcomes of pediatric patients affected by olecranon fractures treated surgically were identified. RESULTS The initial search produced 111 studies, with 8 fulfilling the eligibility criteria of our study. Selected articles (2002-2022) included 122 patients overall. CONCLUSION Displaced olecranon fractures, occurring during skeletal growth and surgically treated, generally have good results, although we are unable to recommend the best surgical treatment based on our review. In most cases, they are intra-articular fractures; thus, the overall goal is to get an anatomic reduction that in some cases cannot be obtained by percutaneous techniques. Tension band suture is the preferred device, although it is not recommended in adolescence for the high risk of fixation failure. Associated lesions may affect results. KEY WORDS olecranon, fractures, children, surgical treatment, upper limb, pediatric